Answer :

Let the three numbers be .


According to the question


…(1)


…(2)


From 2 we get


a3 = 1


a = 1.


From 1 we get



10a + 10ar + 10ar2 = 39r …(3)


Substituting a = 1 in 3 we get


10(1) + 10(1)r + 10(1)r2 = 39r


10r2 – 29r + 10 = 0


10r2 – 25r – 4r + 10 = 0…(4)


5r(2r – 5) – 2(2r – 5) = 0


r = or r =


Now the equation will be




The three numbers are.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The product of thRD Sharma - Mathematics

Express <imRS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

Express <imRS Aggarwal - Mathematics

Prove that RS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

The sum of n termRS Aggarwal - Mathematics

If a, b, c, d areRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

The first term ofRS Aggarwal - Mathematics